Successful case of adjunctive intravenous bacteriophage therapy to treat left ventricular assist device infection. Issue 3 (September 2021) - Tkhilaishvili, Tamta; Merabishvili, Maya; Pirnay, Jean-Paul; Starck, Christoph; Potapov, Evgenij; Falk, Volkmar; Schoenrath, Felix
Highlights: Bacteriophage therapy can be an attractive approach in the fight against MDR infections. The combined antibiotic-phage therapy in addition to surgery leaded to eradication of the chronic LVAD infection. Intravenous bacteriophage therapy was well tolerated without significant side effects.